2021
DOI: 10.31098/jgrcs.v1i1.511
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Mechanisms with Firm Performance: A Study on Malaysia's and Hong Kong's Real Estate Investment Trust (REITs) Public Listed Companies

Abstract: Corporate governance (CG) mechanisms might have a significant effect on firm performance (FP). The purpose of this study was to evaluate if CG mechanisms impact the FP among Malaysia's REITs (M-REITs) and Hong Kong's REITs (H-REITs). The effect of CG's variable on FP can be analyzed by using Panel data analysis. Return on Assets (ROA), Return on Equity (ROE) and Tobin's Q were employed to measure the FP. Data were collected from the annual report available on Bursa Malaysia and the Stock Exchange of Hong Kong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…According to Fariha et al (2022), conflict of interest and the agency cost can be effectively diminished by the decisions made during BM; hence, the BM effectively maximized the shareholders' wealth. The BODs were able to appraise and enhance executive management's current strategies and performance during BM (Ng et al, 2021). BM can measure by the total number of board meetings (Aljaaidi et al, 2021).…”
Section: Relationship Between Number Of Board Meetings (Bm) and Firm ...mentioning
confidence: 99%
“…According to Fariha et al (2022), conflict of interest and the agency cost can be effectively diminished by the decisions made during BM; hence, the BM effectively maximized the shareholders' wealth. The BODs were able to appraise and enhance executive management's current strategies and performance during BM (Ng et al, 2021). BM can measure by the total number of board meetings (Aljaaidi et al, 2021).…”
Section: Relationship Between Number Of Board Meetings (Bm) and Firm ...mentioning
confidence: 99%
“…Even more recently, Soewignyo et al (2021) studied Indonesian RE companies for the period 2015-2019 and reported a statistically insignificant effect of CG factors on firm performance. Concurrently, David et al (2021) assessed the impact of CG mechanisms on Hong Kong and Malaysian REITs and concluded that board size and independent directors on audit committees had a significant effect on Malaysian REIT performance while CEO duality and the number of independent directors had no significant impact on Hong Kong REITs. A critical appraisal of the studies signals a common pathway towards CG-FP research with little emphasis given to the CG adherence levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though compliance with the MCCG 2021 is voluntary, all publicly listed companies are compulsory under the Listing Requirements of Bursa Malaysia Securities Berhad to report in the annual reports as recommended by MCCG 2021. Studies by Ng et al (2021) state that more board diversity will result in better depth and breadth that the board can give compared to non-diverse boards with reference to previous MCCG 2017. Distressed firms' governance characteristics significantly affect the bankruptcy probability (Fich & Slezak, 2008).…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%